RESEARCH PRODUCTION FERMENTED THAI JACKFRUIT JUCE BY USING Lactobacillus plantarum - Nguyen Tan Hung; Truong Thi Tu Tran; Phan Thi Ngoc Hanh (HUIT Journal of Science, 2024)
Jackfruit (Artocarpus heterophyllus Lam) is a fruit with rich nutritional content, rich in vitamins, minerals, and fiber. The objective of this study was to investigate some factors affecting the fermentation of Thai jackfruit juice (black spot) by Lactobacillus plantarum bacteria. The experiment was conducted by investigating the effect of (i) The content of total solids (14 - 22 oBrix); Initial pH (3,8 - 4,2) and (ii) the Initial bacterial ratio (0,5 - 2,0%) to product quality. The results showed that the initial dry matter concentration and pH were adjusted to 18 oBrix and 4,0 to help the fermentation process achieve high efficiency and create products with good sensory quality and good retention of vitamin C and carotenoids. With the initial Bacterial rate of 1%, the fermentation process is effective after 3 days, the product has good organoleptic properties. The product has the characteristic color and taste of the raw materials.